Objectively measured activity patterns among adults in residential aged care - Reid, N.; Eakin, E.; Henwood, T.; Keogh, J.; Senior, H.; Gardiner, P.; Winkler, E.; Healy, Genevieve (2013)
Objectives: To determine the feasibility of using the activPAL3TM activity monitor, and, to describe the activity patterns of residential aged care residents. Design: Cross-sectional. Setting: Randomly selected aged care facilities within 100 km of the Gold Coast, Queensland, Australia. Participants: Ambulatory, older (≥60 years) residential aged care adults without cognitive impairment. Measurements: Feasibility was assessed by consent rate, sleep/wear diary completion, and through interviews with staff/participants. Activity patterns (sitting/lying, standing, and stepping) were measured via activPAL3TM monitors worn continuously for seven days. Times spent in each activity were described and then compared across days of the week and hours of the day using linear mixed models. Results: Consent rate was 48% (n = 41). Activity patterns are described for the 31 participants (mean age 84.2 years) who provided at least one day of valid monitor data. In total, 14 (45%) completed the sleep/wear diary. Participants spent a median (interquartile range) of 12.4 (1.7) h sitting/lying (with 73% of this accumulated in unbroken bouts of ≥30 min), 1.9 (1.3) h standing, and 21.4 (36.7) min stepping during their monitored waking hours per day. Activity did not vary significantly by day of the week (p ≥ 0.05); stepping showed significant hourly variation (p = 0.018). Conclusions: Older adults in residential aged care were consistently highly sedentary. Feasibility considerations for objective activity monitoring identified for this population include poor diary completion and lost monitors.